Pengaruh Sistem Lingkungan Keluarga dan Sekolah terhadap Motivasi Belajar Siswa di MI Muhammadiyah Pasirmuncang - Meti Muji Pangestika; Muh. Hanif (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to analyze the influence of the family and school environment, as well as a combination of both, on student learning motivation at MI Muhammadiyah Pasirmuncang. Learning motivation, as a key factor in student success (Nurrawi et al., 2023), is influenced by the family environment which shapes character and learning habits (Hikmah & Saputra, 2023), as well as the school environment which provides a forum for developing potential and directed learning. This study used a quantitative explanatory research approach (Sugiyono, 2017) with 30 grade 5 students as subjects. The results of the analysis show a significant influence of the school environment on student learning motivation in Islamic Religious Education (PAI) subjects, with a correlation coefficient (rxy) of 0.570 and a determinant coefficient of 32.48%. The regression significance test (tcount = 4.704 > t0.025 = 2.01) strengthens the significance of this effect. A good family environment (average TCR 70.17%) and high learning motivation (average TCR 73.45%) are positively correlated with learning outcomes. Simultaneously, family environment and learning motivation contribute 11.40% to learning outcomes, while the rest is influenced by other factors. This finding is in line with research by Husnan Jamil (2014) and concludes that a positive school and family environment, as well as high learning motivation, are very important to achieve optimal learning outcomes in PAI learning at MI Muhammadiyah Pasirmuncang.